Serving from the top: police leadership for the twenty-first century. Issue 3 (13th November 2017) - Martin, Helen Clare; Rogers, Colin; Samuel, Anthony John; Rowling, Martyn
Abstract : Purpose: The police service in England and Wales faces unprecedented challenges as it moves further into the twenty-first century. Globalisation, increases and changes in types of crime, including cybercrime alongside perennial terrorist threats, coupled with budgetary constraints, mean that the way the police service has traditionally operated needs to change. In part, the police service sees the drive for professionalisation as assisting in providing an efficient and effective answer to the challenges ahead. Previous approaches to leadership styles, based upon hierarchy and rank, may not be the best approach for leaders in such a dynamic and professional organisation. The purpose of this paper is to argue for a debate and a rethink regarding the leadership styles employed by the police in their current role in the context of the influx of new graduate officers. Design/methodology/approach: This paper presents a discursive argument based upon servant leadership (SL) models that aspire to address the multi-faceted challenges faced by the police service. Findings: Leaders in the police service may well consider SL for its ability to release the potential and manage the aspirations of graduate officers. SL is also recognised for its potential in helping the police to better engage with important societal changes that will impact on its organisation and its structure in the future. Social implications: Previous approaches to leadership styles, based upon hierarchy and rank, may not be the best approach for leaders in such a dynamic and professional organisation. This is discussed in relation to a suggested style of leadership. Originality/value: This paper considers the problems faced in leading a professionalised police service and the suitability of a novel approach to leadership, that of the "Servant Leader".